Replacing monensin and virginiamycin with essential oils and short-chain fatty acids in feedlot beef cattle fed a whole shelled corn-based diet: performance, dry matter intake, and ruminal fermentation (Research, Society and Development, 2023)
The objective of this work was evaluating the replacement of monensin and virginiamycin with essential oils and short-chain fatty acids on performance, dry matter intake, and ruminal fermentation in beef cattle fed a whole shelled corn-based diet. A total of 36 young bulls initially averaging 6 ± 2 months old and 257.2 ± 17.2 kg body weight (BW) were allotted to two treatments: 1) diet containing virginiamycin and monensin and 2) diet containing essential oils and short-chain fatty acids. The animals were adapted to the whole shelled corn-based diets by receiving 85% whole corn grain and 15% proteic-mineral pellet for 14 days. The experimental period was of 98 days. Performance, dry matter intake (% BW), feed-to-gain ratio, fecal pH, ruminal pH, and volatile fatty acids in the rumen fluid were assessed. The study was conducted using a completely randomized design. A difference was observed in the average daily gain (P0.05). Regarding volatile fatty acids in ruminal fluid, differences (P